Tools for process modelling in the public administration - Šimonová, Stanislava (Univerzita Pardubice, 2009)
Process modelling serves to present trend of the quality management. The quality management systems have their basis in standards and methods; they can be implemented through the quality certificates. The process definition in the form of process modelling is also the necessary basis for data modelling. But these two modelling approaches have various variants of realization. Implementation of these methods has aim – an increase in quality in processes as well as in data and generally quality in the institution. The question is how the tools and techniques of methods are used and utilized. This paper deals with process approach as the integral part of methods in the area of the Czech public administration.
Keywords: Process management; Modelling; indicators; abstract programming